PRAGMATIC IMPERATIVE FORMS OF BANJAR LANGUAGE IN FLOATING MARKET IN BANJARMASIN - Rissari Yayuk (Hasanuddin University, 2018)
This study on pragmatic imperative forms of Banjar language in floating market in Banjarmasin has two research questions: (1) What are the pragmatic imperative forms of the Banjar language in the Floating Market? (2) What are the pragmatic forms of the Banjar language imperative forms in the Floating Market? The research was a descriptive qualitative study applying Yule and Searle's theory of imperative speech acts. Research techniques used were notes and documentation. The data were analyzed using interpretation technique. This study found that pragmatic imperative forms of Banjar language in floating market are based on their types consisting of imperative command, asking, prohibition, polite forms of requests, command, mutation, allusion. Pragmatic imperative forms in floating market based on their form consist of direct speech act and indirect speech act. In conclusion, the imperative pragmatic forms of Banjar Language in Banjarmasin Floating Market based on their types have sentence structures that are not suitable with the purpose, while based on the imperative pragmatic forms, speakers can directly and indirectly state what they mean to the speech partners.